Recent advancement in the design of mixers for software‐defined radios. Issue 2 (8th November 2021) - Mehta, Shilpa; Li, Xue Jun; Donelli, Massimo
Abstract: The implementation of software‐defined radio necessitates a versatile radio frequency (RF) front‐end that can support multiple standards in different frequency bands. This article presents the state‐of‐the‐art multiband and wideband mixers in the context of different receiver architectures suitable for software‐defined radio (SDR). Wideband and multiband mixer designs reported in the literature are categorized on the basis of their circuit architecture. This study tabulates the results of mixer designs with an emphasis on noise figure (NF), conversion gain (CG), linearity, and image rejection ratio. The best parameters reported in the comparison are 68–84 dB of CG, 3.2 dB of NF, 2.5 mW of power consumption, 12.5 dBm of third‐order input intercept point, and 0.015 mm 2 of area at different frequencies. The study also discusses the design challenges and techniques to overcome those issues. The article concludes with the summary and prospective developments for SDR architectures.